Depressive symptoms among children attending community based support in South Africa – pathways for disrupting risk factors. (October 2020) - Sherr, Lorraine; Yakubovich, Alexa R; Skeen, Sarah; Tomlinson, Mark; Cluver, Lucie D; Roberts, Kathryn J; Macedo, Ana
Children in Southern Africa are exposed to high rates of structural and family adversities. This study tests whether services from Community Based Organisations (CBOs) in South Africa can promote children's resilience against depression exposed to such adversities. Two linked longitudinal studies were conducted, comprising n = 1848 children aged 9 to 13 years. One group received CBO services, whilst the other (quasi-control) did not. Analyses used interaction terms in regression models to test for potential moderation effects of CBO attendance, and marginal effects models to interpret significant interactions. Two interaction effects were shown, demonstrating moderation effects of CBO attendance on common structural disadvantages. First, children exposed to community violence showed increased depression (contrast = 0.62 [95%CI 0.43, 0.82], p < .001), but this association was removed by CBO access (contrast = 0.07 [95%CI −0.28, 0.43], p = .682). Second, children living in informal housing showed increased depression (contrast = 0.63 [95%CI 0.42, 0.85], p < .001), however, this association was removed by CBO access (contrast = 0.01 [95%CI −0.55, 0.56], p = .977). CBO attendance is associated with fewer depressive symptoms, and can buffer against important structural adversities of poor housing and violence that are common in high HIV-prevalence areas. However, CBO attendance was not able to remove the increased psychosocial distress associated with some family-level vulnerabilities such as orphanhood and abuse. These findings highlight the centrality of CBO-provided psychosocial support for children in Southern Africa, and suggest areas for bolstering provision.